3D pharmacophore model studies on ACRB efflux pump inhibitors of Escherichia coli : Khóa luận tốt nghiệp Dược sĩ đại học / Tran Thuy Vy ; Phan Thien Vy science instructor - Tran, Thuy Vy
footnote at the end of the document